Ministry of Justice Synthetic Data First Probation Iteration 2, England and Wales, 2014-2023 (Crime Survey for England and Wales, 2025)
The Ministry of Justice (MoJ) Data First Synthetic Data Project aims to improve engagement with Data First datasets by making synthetic versions of content available to enable more rapid development of research proposals and to thereby enhance the potential for linked administrative data to improve understanding and outcomes across justice systems. The project has led the development of two components: a dataset generation platform and an initial release of lo-fidelity, synthetic data tables. This study includes a synthetically-generated version of the Ministry of Justice Data First Probation datasets. Synthetic versions of all 43 tables in the MoJ Data First data ecosystem have been created. These versions can be used / joined in the same way as the real datasets. As well as underpinning training, synthetic datasets should enable researchers to explore research questions and to design research proposals prior to submitting these for approval. The code created during this exploration and design process should then enable initial results to be obtained as soon as data access is granted. The Ministry of Justice Data First probation dataset provides data on people under the supervision of the probation service in England and Wales from 2014. This is a statutory criminal justice service that supervises high-risk offenders released into the community. The data has been extracted from the management information system national Delius (nDelius), used by His Majesty's Prisons and Probation Service (HMPPS) to manage people on probation. Information is included on service users' characteristics and offence, and on their pre-sentence reports, sentence requirements, licence conditions and post-sentence supervision; for example, age, gender, ethnicity, offence category, key dates relating to sentence and recalls, activities and programmes required as part of rehabilitation (e.g. drug and alcohol treatment, skills training) and limitations set on their activities (e.g. curfew, location monitoring, drugs testing). Each record in the dataset gives information about a single person and probation journey. As part of Data First, records have been deidentified and deduplicated, using our probabilistic record linkage package, Splink, so that a unique identifier is assigned to all records believed to relate to the same person, allowing for longitudinal analysis and investigation of repeat interactions with probation. This aims to improve on links already made within probation services. This opens up the potential to better understand probation service users and address questions on, for example, what works to reduce reoffending. The Ministry of Justice Data First linking dataset can be used in combination with this and other Data First datasets to join up administrative records about people from across justice services (courts, prisons and probation) to increase understanding around users' interactions, pathways and outcomes.